2017
DOI: 10.1016/j.athoracsur.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of a No-Drain Policy After Thoracoscopic Major Lung Resection

Abstract: The outcome of our validation cohort revealed that a no-drain policy is safe in selected patients undergoing thoracoscopic major lung resection and that it may contribute to an early recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
0
26
0
2
Order By: Relevance
“…Interestingly, wedge resection in certain reports was considered to be a risk factor for postoperative air leak. One study limits the number of wedge resections to ≤2, and Ueda et al even excluded wedge resections for omitting chest tube after VATS (14,20,21). In our cohort, we chose the patients with peripheral lesions ≤2 cm, with no obstructive ventilatory defect (FEV1 ≥1.5 L), and with no pleural adhesions for sublobar resections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, wedge resection in certain reports was considered to be a risk factor for postoperative air leak. One study limits the number of wedge resections to ≤2, and Ueda et al even excluded wedge resections for omitting chest tube after VATS (14,20,21). In our cohort, we chose the patients with peripheral lesions ≤2 cm, with no obstructive ventilatory defect (FEV1 ≥1.5 L), and with no pleural adhesions for sublobar resections.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients with wedge resections in ≥3 separate locations and limited the resection size to <2 anatomic segments as a larger residual pleural space would be expected if a larger portion of lung was resected. However, a study of major pulmonary resection under intubated general anesthesia omitting the chest tube has been reported (21). With more experience, tubeless singleport VATS for major pulmonary resection (lobectomy) in selected patients may be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…[1317] Meanwhile, Ueda et al and Murakami et al had reported that they successfully avoided leaving chest tubes during major lung resection through the refined strategy for pneumostasis. [18,19] With regard to children undergoing thoracoscopic operation, Todd had demonstrated that leaving no chest tubes (NCTs) after some no- lung manipulation (ductus arteriosus ligation, congenital diaphragmatic repair, among others) or tiny tissue dissection (lung biopsy) was feasible and allowed for a much more tolerable postoperative course in most children. [6] However, considering the difficulty of dealing with children undergoing thoracoscopic anatomical lobectomy, to date, chest tube placement is a regular procedure, and the chest tube placement time should be at least 1.3 days.…”
Section: Introductionmentioning
confidence: 99%
“…has compared the efficacy of small versus large chest tubes for use in thoracic trauma but no statistically significant difference was found . Recently, Ueda and colleagues reported the validity of their original strategy for omitting chest tube drainage after major lung resection . However, there is no generally accepted approach to chest tube management and clinical experience is still the most important basis in chest tube strategy …”
Section: Introductionmentioning
confidence: 99%